2023
DOI: 10.1681/asn.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

ASH2L Controls Ureteric Bud Morphogenesis through the Regulation of RET/GFRA1 Signaling Activity in a Mouse Model

Abstract: Significance Statement Causes of congenital anomalies of the kidney and urinary tract (CAKUT) remain unclear. The authors investigated whether and how inactivation of Ash2l—which encodes a subunit of the COMPASS methyltransferase responsible for genome-wide histone H3 lysine K4 (H3K4) methylation—might contribute to CAKUT. In a mouse model, inactivation of Ash2l in the ureteric bud (UB) lineage led to CAKUT-like phenotypes. Removal of ASH2L led to deficient H3K4 trimethylation, which slowed cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…PLOS BIOLOGY expression level (Fig 4G). Considering that although it has been reported that depletion of any component of the WRAD complex results in the global loss of H3K4 methylation to varying degrees [47][48][49], WRAD complex tends to be complicated with the evolution of species, and there might be other variable factors in different complexes [50]. Based on our current results, we could only preliminarily conclude that TOX3 was involved in the establishment and maintenance of the stem-like traits of CRC cells mainly by facilitating the transcription of ABCG2 via recruiting WDR5 and its subsequent promotion on the tri-methylation of H3K4 at ABCG2 promoter region.…”
Section: Plos Biologymentioning
confidence: 99%
“…PLOS BIOLOGY expression level (Fig 4G). Considering that although it has been reported that depletion of any component of the WRAD complex results in the global loss of H3K4 methylation to varying degrees [47][48][49], WRAD complex tends to be complicated with the evolution of species, and there might be other variable factors in different complexes [50]. Based on our current results, we could only preliminarily conclude that TOX3 was involved in the establishment and maintenance of the stem-like traits of CRC cells mainly by facilitating the transcription of ABCG2 via recruiting WDR5 and its subsequent promotion on the tri-methylation of H3K4 at ABCG2 promoter region.…”
Section: Plos Biologymentioning
confidence: 99%